Conciliación de medicamentos en pacientes con Patologías Crónicas. Servicio Medicina Interna. HANM periodo enero – abril 2023 - Poveda Villena, Erika Alexandra (2023)
Medication reconciliation is a process that consists of detailing and comparing each of the medications that the patient usually takes with the one prescribed during admission to a hospital unit or before a transfer, with the purpose of resolving discrepancies found and preventing errors. in medication or adverse events, for this reason the objective of this research work was to evaluate the application of the medication reconciliation protocol in patients with chronic pathologies in the internal medicine service of the Alfredo Noboa Montenegro Hospital January 2022 - April 2023, using a descriptive, observational, retrospective, cross-sectional, documentary and field methodology, the study population was 155 medical records and 10 nursing professionals from the hospital's internal medicine service, a sample with which the entire research project was developed, as technique and data collection was an instrument for the audit of the clinical history and a survey of 17 questions applied to the nursing professional, the results were 100% comply with the reconciliation of medications in patients with chronic pathologies, but there are deficiencies when to knowledge and when the most prevalent chronic diseases are arterial hypertension with 44%, diabetes mellitus with 29% and therefore COPD with 16%. Keywords: Medication reconciliation, chronic patients, arterial hypertension, mellitus diabetes.